Strategi Komunikasi Politik Untuk Memperoleh Dukungan Pemuda Dalam Pilkada Kota Serang: Studi Pada Pasangan Calon Syafrudin-Subadri - Mohamad Ikrom Arasid; Yusa Djuyandi; R. Widya Sumadinata (Faculty of Social and Political Sciences, Universitas Muhammadiyah Malang, 2022)
Abstract A group of young people ventured to openly support the candidate pair Syafrudin-Subadri in the 2018 Serang City Regional Head General Election. Syafrudin-Subadri is an opponent of the incumbent family and a member of the Banten political class supported by the majority coalition. Rationally, the incumbent family has more political possibilities and power because it is supported by the majority coalition and is a member of the incumbent's family and the Banten political elite. The goal of this research is to describe and assess Syafrudin-political Subadri's communication strategy for gaining support for youth organizations in the 2018 Serang City Regional Elections, as well as the youth group's basic foundation. The conceptual basis for this research is the theory of political communication strategy with three approaches, namely maintaining the character and strengthening institutions, creating togetherness, and building consensus. This research method uses descriptive qualitative methods with a case study approach and uses purposive data collection techniques to obtain in-depth information. The research subjects are Syafrudin, the elected mayor and the object of the Serang City Youth Network. This paper examines the candidate pair Syafrudin-Subadri got youth support since they were deemed credible and of high quality. Political messages are delivered to the Syafrudin-Subadri pair using direct or face-to-face persuasive tactics, with media chosen based on the era and societal conditions. The Syafrudin-Subadri duo may then grasp the audience, particularly among the youth, by conditionally and more dominantly absorbing ambitions from diverse circles of society.